Induksi Tunas Karamunting (Rhodomyrtus tomentosa) secara Invitro - Mela Rahmah (Mahesa Research Institute, 2023)
Tissue culture techniques provide an alternative to vegetative plant propagation efforts in conservation efforts for Karamunting, the existence of which is becoming increasingly rare. The explant as the material used is the result of in vitro germination using several concentrations of GA3. This research was structured in the form of a factorial experiment with a completely randomized factorial design (RAL) with 2 factors. The first factor is the BAP concentration with three levels, namely B1 = BAP 0.5 B2 = BAP1 ppm and B3 = BAP 1.5 ppm. The second factor is the concentration of TDZ with three levels, namely T1 = TDZ 0 ppm, T2 = TDZ 0.25 ppm and T3 = TDZ 0.5 ppm. The results of the research showed that there was an interaction between the growth regulators BAP and TDZ on the percentage of live explants and the height of karamunting explants. In terms of the percentage of live explants, giving BAP 0.50 ppm without TDZ is the best concentration with a live percentage of 100%. Treatment of 1 ppm BAP and 0.25 ppm TDZ produced the highest shoots, namely 2.83 mm. The time of emergence of shoots and the number of shoots per explant had no interaction and the influence of a single factor, several concentrations of BAP and TDZ.